BS EN 16798-5-1 AMD1. Energy performance of buildings - Ventilation for buildings. Part 5-1. Calculation methods for energy requirements of ventilation and air conditioning systems (Modules M5-6, M5-8, M6-5, M6-8, M7-5, M7-8). Method 1: Distribution and generation (23rd December 2019) - British Standards Institution,
No abstract available